Kajian Pengaruh Fraksi Volume Serat Akibat Perlakuan Alkali Terhadap Ketangguhan Impak Komposit Limbah Serat Aren-Polyester - Wijoyo, Wijoyo; Nurhidayat, Achmad; Purnomo, Catur (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
The purpose of this study is to investigate the influence of fiber volume fraction of the impact strength of palm fiber-unsaturated polyester composite and investigate the mechanism of fracture caused by impact loads. This research material is palm fiber (Arenga pinnata), unsaturated polyester matrix yukalac BQTN-EX 157 type, hardener metyl etyl ketone peroxide (MEKPO), alkali solution (NaOH) and H2O. Testing with Charpy impact tester, impact test specimens prepared according to standard test ASTM D-5942. While the macro picture is used for the analysis of the fracture. The results showed that the most optimum impact toughness of palm fiber-polyester composite reached 0.011 J/mm2 on volume fraction (Vf) 40%. While the interaction characteristics of palm-fiber bond strength polyester showed matrix cracking behavior of failure on volume fraction (Vf) 10% to 30%, and fiber pull out the volume fraction (Vf) 40% and 50%, the same fracture behavior between the matrix and fibers in volume fraction (Vf) 40% indicates that fiber and matrix has a strong bonding interaction.